Positive youth development: a measurement framework for sport - Vierimaa, M.; Erickson, K.; Côté, J.; Gilbert, W. (International Journal of Sports Science and Coaching, 2012)
The 4Cs of positive youth development (PYD; competence, confidence, connection, and character) have been advocated as desirable athlete outcomes of sport participation, and in effect, a useful proxy measure of coaching effectiveness. However, a shortcoming of this framework has been a lack of tangible ways to accurately measure these constructs in athletes. This article reviews the sport literature and presents a concise toolkit made up of existing questionnaires and measurement techniques that can collectively be used to assess coaches' ability to facilitate PYD in athletes in organized youth sport settings. This integrative approach to the measurement of PYD in athletes is not designed to replace similar questionnaires in sport, but is simply a measurement approach grounded in the PYD literature that can be applied across a range of sport contexts. Implications for the use of this framework and toolkit in both coaching research and practice are discussed.